PENGARUH NILAI TUKAR RUPIAH DAN LEVERAGE TERHADAP KEPUTUSAN HEDGING PADA PT KRAKATAU STEEL (PERSERO) TBK PERIODE 2015 – 2024 - Sisca Amelia; Eni Puji Astuti (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of the rupiah exchange rate and leverage on hedging decisions at PT Krakatau Steel (Persero) Tbk for the period 2015–2024. The study uses a quantitative method with data obtained from the company's financial statements and Bank Indonesia data. The results show that the rupiah exchange rate has a significant effect on hedging decisions, evidenced by a significance value of 0.026 (<0.05) and a calculated t of -2.826 greater than the t table of 2.365. Leverage does not have a significant effect because it has a significance of 0.874 (>0.05) and a calculated t of 0.164 smaller than the t table. Simultaneously, the exchange rate and leverage also do not have a significant effect on hedging decisions, with an F count of 4.387 <F table of 4.740 and a significance of 0.058 (>0.05). These findings indicate that exchange rate fluctuations are a major factor in the company's hedging decisions, while leverage does not have a significant contribution in the decision-making process.